ANALISIS PENGARUH CELEBRITY ENDORSER, DAYA TARIK IKLAN, KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen yang Menggunakan Masker Wajah Mustika Ratu di Kota Semarang) - Hestyani, Andriana Dwi; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2017)
Indonesia is one of region which have potentials on developing beauty products market especially on cosmetics and that pursued a lot of new brands for keep coming out. This matter makes the market competition get tigher and indirectly forced business for always have ways to survive. One of the biggest brand on cosmetics industry is Mustika Ratu, as a 25th yeas old brand, Mustika Ratu should be superior in matter of this competition and one the way to stay as superior is to make their customers keep on buying Mustika Ratuâ€™s products. This study aimed to analyze the influence of celebrity endorser, advertising appeal, product quality to purchase decision of face mask Mustika Ratu using brand image as intervening variable. This study is conducted on all Mustika Ratu face maskâ€™s customers in Semarang.Purposive sampling method is used for this research, samples were collected from 100 respondents (consumer who use face mask Mustika Ratu and who watch advertising of Mustika Ratu). Multiple regression analysis is used for this study.This results showed that celebrity endorser, advertising appeal and product quality has positive and signifcant effect on brand image (as intervening variable), and brand imageÂ has positive and significant effect on purchase decision.